Educação psicossomática no contexto pedagógico das práticas de educação física - AZEVEDO, Ediane Souza de (2019)
This work deals with literature and the school physical education, bringing both your concept and history, so that they are articulated and medias to result in new pedagogical education look: physical and mental health education in school, thereby, the aim is to objectively draw the theories of physical education by following the ideas of Medina (2007) and Brandil (2000) subsequently to the psychosomatic theories second son and Burd (2010), Cruz and Junior (2011) and Silva and Gaio (2016) to show a new proposal and perspective of education aimed at discussing about physical and mental health with students (young teenagers) so they have a renewed understanding of meaning to this day have health and wellness; in how to take care of your I fully, preventing them from psychological and physical diseases arising out of this generation, so this research follows the methodology of bibliographical nature and qualitative research, seeking for new thoughts and arguments supporting both the content so that the ideas presented in this project has meaning and demonstrate validity for education.